Application of Growth Monitoring System Web Based to Monitor Growth toodler - Rahmawati, Triana; Assalim T.P, M. Prastawa; Soetjiatie, Liliek (Frontiers in Community Service and Empowerment, 2025)
The community service program "Implementation of a Web-Based Growth Monitoring System Tool for Monitoring the Growth and Development of Toddlers" aims to introduce and implement a web-based Growth Monitoring System (GMS) tool in monitoring the growth and development of toddlers effectively and accurately. Partners in this community service program are actors health workers and posyandu cadres in the Kenjeran Community Health Center area, Kenjeran Village, Bulak District, Surabaya City. Through this system, health workers and parents can access toddler growth data, such as weight, height and nutritional status, in real-time. It is hoped that this activity can increase public awareness regarding the importance of monitoring children's growth and development, as well as help detect early nutritional problems or suboptimal growth, so that treatment can be carried out more quickly and precisely. The results of this service activity show that the application of a web-based Growth Monitoring System (GMS). has helped improve monitoring of toddler growth and development in target communities. Health workers and parents can now access toddler growth data more easily, structured and in real-time. This system makes it easier to detect nutritional problems or growth disorders early, so that treatment can be taken more quickly. Community participation in these activities has also increased, with a better understanding of the importance of monitoring children's growth and development to ensure the well-being and health of toddlers.